Effect of Using Different QoS Parameters in Performance of AODV, DSR, DSDV AND OLSR Routing Protocols In MANET - Norrozila, Sulaiman; Osamah, I. Khalaf; Ghaidaa M., Abdilsahib; Mohammed, Muamer N.; Ayoob, Ayoob A. (SEEK Digiltal Library, 2014)
Many routing protocol methods have been proposed in Mobile Ad-Hoc Network but still the challenges are to improve the routing performance. In small or medium ad hoc networks flat protocols can be used but in case of large networks more complicated routing protocols are needed to be used in order to be suitable with them. Since the Ad-hoc networks have many constrains in bandwidth and battery life so the routing protocol which is used must be done its work correctly without using much resources of network by its overhead traffic. This paper, focus on investigation the performance analysis of four important routing protocols in mobile Ad hoc networks such as AODV (Ad- Hoc On-Demand Distance Vector), DSR (Dynamic Source Routing Protocol), DSDV (Destination Sequenced Distance-Vector), and OLSR (Optimized Link State Routing Protocol). The analysis of performance is made on QoS parameters such as the basis packet delivery ratio, throughput, and end-toend delay, the simulator used is NS-2.